Effect of degree of milling on the cadmium in vitro bioaccessibility in cooked rice. Issue 11 (29th September 2020) - Peng, Lanlan; Chen, Jiwang; Chen, Lu; Ding, Wenping; Gao, Yonggui; Wu, Yongning; Xiong, Youling L.
Abstract : Abstract: Cadmium (Cd) contamination in rice grain is common worldwide. This study investigated the effect of degree of milling (DM) on the reduction of Cd in cooked rice grain and porridge (rice‐to‐water ratios 1:1.6 and 1:10, respectively) and Cd in vitro bioaccessibility. Cd‐contaminated rice grains with DMs of 20%, 15%, and 0% were cooked and then subjected to successive digestion in a gastrointestinal environment model. Simulated‐digestion juices, including saliva, gastric juice, duodenal juice, and bile juice, were used. The degree of gelatinization of cooked rice was measured and the morphological characteristics of the grain were also examined. The results showed that the Cd in vitro bioaccessibility, although less than 50% in all samples, was gradually increased with an increase of DM. The detected Cd bioaccessibility was higher at half meals (reduced grain content) when compared with full meals (full grain content). As DM increased, the surface of cooked rice grain and porridge became smoother, and the amount of fiber, fat droplets, and starch granules were gradually decreased, whereas degree of gelatinization increased. The results indicate that DM affects the Cd in vitro bioaccessibility in cooked rice by altering the gelatinization of starch. Practical Application: Degree of milling (DM) significantly influenced the in vitro bioaccessibility of cadmium (Cd) in cooked rice. This work may offer a potential solution to the rice grain with high Cd content because a limited DM will allow a low bioaccessibility of Cd.